EFFECTIVENESS OF ACETYLSALICYLIC ACID IN CORRECTION OF POST-STROKE FATIGUE DURING ACUTE CEREBROVASCULAR EVENTS - I.I. Delva (Проблеми екології та медицини, 2019)
Post-stroke fatigue (PSF) is a common and often debilitating sequela of strokes that affects more than one third of stroke patients. Recent investigations revealed etiologic and pathogenetic heterogeneity of PSF depending on the time after acute cerebrovascular event (ACE). PSF that occur during acute stroke is associated predominantly with biological factors, including stroke-inducing immune and inflammatory reactions. In particular, we found significant associations between clinical features of PSF and certain regularities of C-reactive protein (CRP) and interleukin (IL)-1β levels in blood serum during the first 3 months after ACE occurrence. Given that there is not a clearly defined etiology for PSF, there are no rationally informed interventions. Іf dysregulation of the immune response isan important contributing factor to PSF, interventions that lessen inflammation would be appropriate treatment strategies. Іt would be reasonable to consider ASA, albeit at a higher dose than is normally used for secondary stroke prevention, as a treatment for PSF. Thus, it is advisable to study effects of ASA at the anti-inflammatory dose (300 mg a day) on markers of system inflammation an don PSF clinical course during the first 3 months after ACE occurrence. Objective: to study effectiveness of ASA at the anti-inflammatory dose (300 mg a day) on PSF clinical course and ASA effects on markers of system inflammation during the first 3 months after acute cerebrovascular event (ACE) occurrence. We recruited in the study 39 in hospital patients with ischemic strokes and transient ischemic attacks (TIA) who needed to take acetylsalicylic acid (ASA). All patients had been diagnosed with PSF within the first 3 days after ACE onset. PSF was diagnosed by use of questionnaire – Fatigue Assessment Scale (FAS). We formed two groups of patients. The first group (control PSF group) consisted of 24 patients who used ASA according to «Unified clinical protocol for medical care. Ischemic stroke (emergency, primary, secondary (specialized) medical aid, medical rehabilitation)» - after excluding hemorrhagic stroke by neuroimaging it was started ASA intake in the doses of 150-300 mg a day enterally during hospital stay with subsequent intake of 75-150 mg a day (prophylactic dose) continuously after hospital discharge. The second group (ASA PSF group) had 15 patients who started to use ASA just after excluding hemorrhagic stroke in the dosage of 300 mg a day for 3 months with subsequent dose reduction to 75-150 mg a day (prophylactic dosage) continuously. Diagnosis of PSF presence/absence, measurement of PSF severity and simultaneous measurement of systemic inflammatory markers in blood serum were carried out at the certain time points after ACE onset: at the first 3 days, at 1 month and at 3 months. Concentrations of СRP, IL-1β andIL-6 in blood serum were measured by enzyme-linked immunosorbent assay. The use of ASA in the dose of 300 mg a day during 3 months in patients who had been diagnosed with PSF within the first days after ACE occurrence is associated with significant decreasing of PSF intensity due to FAS in comparison with using of preventive ASA doses. The use of ASA in the dose of 300 mg a day during 3 months after ACE occurrence is associated with significant modification of post-stroke inflammatory response in form of CRP and IL-1β blood level changes.